Microelectromechanical system-based electrochemical seismic sensors with an anode and a cathode integrated on one chip. (12th December 2016) - Deng, T; Sun, Z; Li, G; Chen, J; Chen, D; Wang, J
Abstract: This paper presents a microelectromechanical system (MEMS)-based electrochemical seismic sensor with an anode and a cathode integrated on a single chip. The proposed approach decreases the number of requested wafers as the sensing unit from seven to two. In addition, no alignment and no bonding among the electrodes are needed, significantly simplifying the fabrication process. The experimental results indicate that the proposed device produced a sensitivity of 5771.7 V (m s −1 ) −1 at 1.4 Hz and a noise level of  −163 dB (i.e. 7.1 (nm s −1 )/Hz 1/2 ) at 1 Hz. Moreover, the proposed device effectively responds to random ground motions, enabling the detection of low-frequency seismic motions caused by earthquake events.